2004
DOI: 10.1186/cc2934
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In patients with acute respiratory distress syndrome (ARDS), the lung comprises areas of aeration and areas of alveolar collapse, the latter producing intrapulmonary shunt and hypoxemia. The currently suggested strategy of ventilation with low lung volumes can aggravate lung collapse and potentially produce lung injury through shear stress at the interface between aerated and collapsed lung, and as a result of repetitive opening and closing of alveoli. An 'open lung strategy' focused on alveolar patency has th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 46 publications
2
42
2
Order By: Relevance
“…6%), Staphylococcus species (17.4%), Staphylococcus aureus (11.6%), Proteus species (11.6%), Pseudomonas aeruginosa (10.1%), Candida species (10.1%), Enterobacter species (7.2%), Klebsiella species (4.3%) and Candida albicans (2.9%). This agrees with the findings of LAUPLAUD et al 11 which gave the percentage of E. coli implicated in urine of patients in Calgary Health Region Intensive Care Unit in Canada as 23%. Only 2.9% of Candida albicans were recovered compared to 20% found by LAUPLAUD and co-workers 11 suggesting that they were not nosocomial infections.…”
Section: Discussionsupporting
confidence: 92%
“…6%), Staphylococcus species (17.4%), Staphylococcus aureus (11.6%), Proteus species (11.6%), Pseudomonas aeruginosa (10.1%), Candida species (10.1%), Enterobacter species (7.2%), Klebsiella species (4.3%) and Candida albicans (2.9%). This agrees with the findings of LAUPLAUD et al 11 which gave the percentage of E. coli implicated in urine of patients in Calgary Health Region Intensive Care Unit in Canada as 23%. Only 2.9% of Candida albicans were recovered compared to 20% found by LAUPLAUD and co-workers 11 suggesting that they were not nosocomial infections.…”
Section: Discussionsupporting
confidence: 92%
“…The research showed that, during the past 10 years, Candida spp. was more often being isolated as an etiologic factor of those infections, 20 to 44.4% (12, 13). …”
Section: Discussionmentioning
confidence: 99%
“…Recruitment maneuvers (RMs) can prevent lung collapse by temporarily increasing transpulmonary pressure (9). Animal studies show that RMs improve oxygenation and may attenuate derecruitment-associated lung injury (10, 11).…”
mentioning
confidence: 99%
“…Animal studies show that RMs improve oxygenation and may attenuate derecruitment-associated lung injury (10, 11). However, the efficacy of RMs in adults and pediatrics remains controversial (9). Some studies suggest a benefit in mortality and physiological parameters such as oxygenation and dynamic respiratory system compliance (6, 1228).…”
mentioning
confidence: 99%
See 1 more Smart Citation